Management of Zakat in Reducing Poverty in Pekanbaru - Zulkifli Zulkifli; Maghfirah Maghfirah (Journal of International Conference Proceedings, 2022)
Zakat has excellent potential to alleviate poverty and improve people's welfare. If zakat can help reduce poverty in a country. Assets are believed to be able to help the poor overcome difficulties in meeting their basic needs. If the distribution of these assets can result in productive activities, it will be more optimal. This article aims to analyze the management of Zakat in reducing poverty in Pekanbaru. This research is a descriptive-qualitative research method with a critical paradigm approach in a case study. The primary data collection method is observation, structured interviews, and documentation. While, Data processing and analysis techniques are data reduction, data presentation, conclusion drawing, and verification. While testing the validity of the data is done by testing the credibility. The result of this article is thatÂ zakatÂ management has not been implemented optimally in alleviating poverty because; (1) the provision of zakat funds is still temporary or short-term assistance, (2) the management is not well organized, (3) the distribution of zakat funds for effective programs is still in small amounts when compared to other distribution portions, and (4) the distribution of zakat funds for effective programs, it is not based on the results of a comprehensive study and is accompanied by supervision from Badan Amil Zakat Nasional